Novel Framework for Software Designing to Create Reliable and Re-Usable Components - Saini, Gurpreet Singh; Dubey, Sanjay Kumar; Bharti, Sunil Kumar (International Journal of Computing and Digital System (Jāmiʻat al-Baḥrayn. Markaz al-Nashr al-ʻIlmī), 2020)
Re-usability & Reliability are eminent factors in development of new software's to control the increasing costs and development period. The suppliers need to customize software as per the customers, however managing the same using re-usable components is a difficult task and determining their reliability is a much tougher job. While using the re-usable code, the focus lies on the coding or low-level design such that it can be merged easily with the new code. Though, it may be one of the options to chalk out a customized solution but focus has to be put on functional requirement during the development period. These components with reusable need are to be developed with utmost care due to high degree of cohesion and less degree of coupling to other modules with higher reliability factor. The novel framework discussed in this paper describes one such strategy wherein a module can be developed with less coupling to the modules of the software's being developed and reliability as one of the prime focus. The framework possesses the ability to customize the development dependent upon the nature of the product under work. Hence, customizing the re-usable component makes it quick to develop with few modifications at the functional and parametric level. These Re-usable components also lead to short development time-periods along with man hours. Less modifications in modules will also lead to clear testing and hence, less no. of bugs leading to low maintenance costs of the product. The paper also focusses the areas which can use this strategy for development in Future scope section as summary. Keywords: Software Reuse, Software Re-Engineering, Software Reliability, Software Project Management, Functional Paradigm